The Role of Geothermal Waters in Sustainable Development Application of Main North Center Algerian Hot Springs (Righa, Biban, Ksena) - A. Issaadi, A. Ait Ouali.; K. Imessad, A. Ayadi (European Journal of Sustainable Development, 2019)
The study zone is one of the significant thermal waters in the north Algeria. It is characterized by a cold climate with intense rain rates 700 mm/year. The Jurassic geothermal reservoir system is exploited by thermal springs and traditional wells for agricultural purposes. The main reservoir lithology characterized by calcareous formations which yield the chemical features of highly mineralized Na-Cl type representing the thermal waters. Seven main Hot springs was samples collected June 2018 with a temperature average between 29 and 80° C and conductivities range from 2520 to 3766 ?S/cm.For a better application of geothermal water sites, a multidisciplinary methods was adopted, geological site study, water chemistry and touristic impact for local economic development. In this study, a final map was realized of geothermal potential for possible exploitation of this clean energy Keywords: Biban, thermal springs, sustainable development, geothermal use, water chemistry